EFL Students’ Problem in Speaking Activity: A Case Study in English Students of English Department - Anugrah, Ramdan (Papanda Journal of English Education, 2022)
The aims of this research are to reveal the problems faced by students in speaking English. The research applied case study approach. Eighteen students of English education were selected as the participants of this research. The instruments used to collect the data was questionnaire. The questionnaire used was adapted from another researcher. The writer used content-related validity and triangulation to the questionnaire. The result found that students encountered problem in speaking class of English Education Study Program. The result of the questionnaire that distributed to the participants showed that Lack of the Vocabulary is the highest result. The second highest is the pronunciation. The third is fluency. The fourth is Fear of Mistake. The writer also found that The Lack of Motivation is not a problem for the students in the 8th semester of English Education Study Program.